(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
In today’s education system, distance learning is becoming a convenient form of education. Distance education is a form of education in which, in addition to full-time and part-time education, the preferred traditional and innovative methods, tools and forms of education based on computer and telecommunication technologies are widely used in the information process. The educational process is organized in a place that is convenient for the student, based on an individual schedule, with the help of special facilities, telephone, electronic communication and other educational tools.